Program Pemberdayaan Dan Kesejahteraan Keluarga Dalam Mewujudkan Kemandirian Ekonomi Keluarga - The, Janny; Oja, Hubertus (Universitas Musamus, Merauke, Papua, 2024)
PKK is an empowerment movement that seeks for the economic independence of the community. The purpose of this study is to determine the Family Empowerment and Welfare program in realizing family economic independence in Kampung Kuler. The research method used is a qualitative method with a descriptive approach. The results showed that the PKK program in Kampung Kuler related to the skills program in the form of training that was carried out was effective but not optimal due to low awareness, responsibility and commitment to be involved in planning and implementing activities, initiatives and cooperation to continue alone and together is still low, continuous assistance from the village government does not yet exist, besides that there are also difficulties in marketing skill businesses, road access and communication networks have not been supported and there is no cooperative presence. So it can be seen from the indicators of process evaluation in planning and implementing activities not all mothers are involved, assistance and supervision from the village government are carried out only during the training period. In the benefit evaluation indicator, already providing income can also increase knowledge and skills, but not all mothers feel it. Then the consequence evaluation indicators, mothers can now help their husbands make a living, do not continue to hope for the help of the closest people to meet their needs, have knowledge and skills also have their own income even though they only meet basic needs but have not all experienced it..